INVESTIGATION OF NATURAL CONVECTION HEAT TRANSFER AT CONSTANT HEAT FLUX ALONG A VERTICAL AND INCLINED PLATE - Yildiz, Sebiha (YILDIZ TECHNICAL UNIV, 2018)
It is a common phenomenon that the devices that are exposed to constant heat fluxes are cooled at natural atmospheric environments. However, it is required to know the surface temperature in these devices. In this study, the cooling of a plate (1 m in height and 1 m in width) which is oriented vertical, and also 20 degrees- and 45 degrees-inclined from the vertical (downward-facing surface), at the constant heat flux of 1000 Wm(-2) at atmospheric natural convection conditions is investigated. The local temperature values at the vertical center of the plate are calculated using the correlation in Vliet [1]'s experimental study and computer analyses and compared to those results. The results show that the surface temperature values of the plate at the inclination angle of 45 degrees are relatively higher than those of the plate at the vertical state and those of the 20 degrees-inclined plate.
Keywords: Natural Convection; Computer Analysis; Vertical and Inclined Plate; Downward-Facing Surface; Constant Heat Flux; Air; SURFACES; EFFICIENCY; Thermodynamics